Single-Incision vs. Conventional Laparoscopic Surgery for Colorectal Cancer: An Update of a Systematic Review and Meta-Analysis - Yuan, Ye; Jian, Jianing; Jing, Hailiang; Yan, Ran; You, Fengming; Fu, Xi; Du, Linke; Li, Wenyuan (Frontiers in Surgery, 2021)
Although the advantages of single-incision laparoscopic surgery have been reported in several meta-analyses, the low quality of studies included in the meta-analyses limits the reliability of such a conclusion. In recent years, the number of RCTs on the efficacy of SILS in colorectal cancer has been on the rise. This update systematic review and meta-analysis aims to compare efficacy and safety of SILS and CLS in the patients with colorectal cancer. Methods: Relevant data was searched on the CNKI, Wanfang, VIP, Sinomed, PubMed, Embase, and Cochrane CENTRAL databases from inception until February 5th, 2021. All RCTs comparing SILS and CLS were included. The main outcomes were 30 days of mortality, postoperative complications, intraoperative complications, whereas secondary outcomes were the number of lymph nodes removed, duration of hospital stay, intraoperative blood loss, abdominal incision length, reoperation, readmission, conversion to laparotomy, operation time and anastomotic leakage. Results: A total of ten RCTs were included, involving 1133 participants. The quality of the included studies was generally high. No significant difference was found between SILS and CLS in the 30 days mortality rate. The results showed that SILS group had a lower rate of postoperative complications (RR = 0.67, 95%CI: 0.49 to 0.92), higher rate of intraoperative complications (RR = 2.26, 95%CI: 1.00 to 5.10), shorter length of abdominal incision (MD = -2.01, 95%CI: -2.42 to -1.61) (cm), longer operation time (MD = 11.90, 95%CI: 5.37 to 18.43) (minutes), shorter hospital stay (MD = -1.12, 95%CI: -1.89 to -0.34) (days) compared with CLS group. However, intraoperative blood loss (MD = -8.23, 95%CI: -16.75 to 0.29) (mL), number of lymph nodes removed (MD = -0.17, 95%CI: -0.79 to 0.45), conversion to laparotomy (RR=1.31, 95%CI: 0.48 to 3.60), reoperation (RR = 1.00, 95%CI: 0.30 to 3.33) and readmission (RR =1.15, 95%CI: 0.12 to 10.83) and anastomotic leakage were not significantly different between the groups. These results indicate that SILS did not has a comprehensive and obvious advantage over the CLS. Surgeons and patients should weigh the pros and cons of the two procedures. Further RCTs are needed to prove long-term outcomes of SILS in colorectal cancer.